Investigating dominant and passive students on pair work towards the students’ writing performance - Styati, Erlik Widiyani; Latief, Mohammad Adnan (Penerbit Universiti Kebangsaan Malaysia, 2018)
The research aims to investigate the significant difference between the mean scores of the writing performance of the students working in the dominant-dominant pairs (DDP) and those working in the dominant-passive pairs (DPP). It investigates the effectiveness of pair work to reveal in what pair the students have a better-writing performance. The experimental design using pretest-posttest design was used in this study. The writing performance of the students working in the dominant-dominant pairs (DDP) and those working in the dominantpassive pairs (DPP) was compared. The subjects of the study were the students of the English Department of private University in Madiun, East Java, Indonesia who were in their fourth semester. The current study employed the standardized proficiency writing test which was adopted from the TOEFL-Test. Descriptive statistics and inferential statistics were chosen to answer the research question. Independent t-test by using SPSS 17.0 was employed to see whether there was a significant difference in the mean scores between the students working in the dominant-dominant pairs (DDP) and those working in the dominant-passive pairs (DPP). The result shows that the students who work in the dominant-dominant pairs (DDP) perform better at writing performance than the students who work in the dominant-passive pairs (DPP). Furthermore, pair work provides the students with more opportunities to engage with one another to share ideas in writing. Thus, the teacher should arrange the best group of classification at the beginning of making a pair work before the students are asked to have a discussion in writing.